The genus Ageratina (Eupatorieae, Asteraceae) in Ancash department, Peru - Navarro, Eduardo (2025)
A total of 10 species of Ageratina Spach were found in the Ancash department, grouped in two subgenera, Ageratina and Apoda R.M.King & H.Rob. Two species are new reports for the department, Ageratina bishopii R.M.King & H.Rob. and A. proba (N.E.Br.) R.M.King & H.Rob. Six are endemic to Peruvian territory. The greatest diversity of species is found between 3100 – 4300 m in shrubby and rocky-stony slopes. Dichotomous keys for the subgenera and species are provided. A brief description of information on the ecology, distribution and material examined of each species is included as well common names and uses.